Adaptive governance in the developing world: disaster risk reduction in the State of Odisha, India. (16th March 2019) - Walch, Colin
Abstract : Under what conditions do governments turn to adaptive governance systems? This paper explores a success case of adaptive governance in a non-western country and tries to understand what factors lead to the adoption of this type of governance. Adaptive governance is considered most efficient to address the many challenges of climate change and natural disasters because it embraces uncertainty by focusing on collaboration, flexibility and learning. Yet, the concept remains underdeveloped and the conditions under which governments decide to embrace adaptive governance are not clear. The paper argues that two main factors are crucial for governments to turn to adaptive governance. First, a traumatic shock is likely to stimulate a reconsideration of the manner in which governance is thought and applied. The shock by involving considerable economic and human cost creates a momentum for governance rethinking. Second, a committed political leadership is essential to make use of that momentum to reform previous governance practices to create a more resilient system. These arguments are explored in the case of Odisha, an Indian state that was able to adopt adaptive governance and that became a successful example of disaster risk reduction and climate change adaptation.